An Association Between Perceived Social Support and Posttraumatic Stress Symptom Severity Among Women With Lifetime Sexual Victimization: The Serial Mediating Role of Resilience and Coping. (December 2020) - Hirai, Michiyo; Charak, Ruby; Seligman, Laura D.; Hovey, Joseph D.; Ruiz, John M.; Smith, Timothy W.
This study examined the association between perceived social support and severity of posttraumatic stress symptoms, serially mediated by resilience and coping among women exposed to different patterns of sexual victimization experiences: childhood sexual abuse (CSA) only, adult sexual assault (ASA) only, and sexual revictimization (SR). A total of 255 sexually victimized women recruited from four U.S. universities completed self-report measures online; 112 participants reported provisionally diagnosable levels of symptoms of posttraumatic stress disorder (PTSD). The proposed model was largely supported in the CSA only group and the SR group. Different patterns of mediational effects were found across the three groups. Clinical and theoretical implications are discussed.